Mechanisms of development of antipsychotic-induced metabolic disorders: pharmacogenetic aspect - R. F. Nasyrova; M. Yu. Tolmachev; D. A. Sychev; K. K. Yakhin; N. G. Neznanov (Бюллетень сибирской медицины)
Antipsychotics are the main drug group in the treatment of disorders of the schizophrenic spectrum. At the same time, this drug group requires long-term use, has a narrow therapeutic breadth and a large spectrum and high severity of undesirable drug reactions, the manifestation of which is largely determined by the patient’s genotype. In this connection, the severity of undesirable drug reactions in drugs of the first and second generation of antipsychotics is different. Atypical antipsychotics, unlike typical antipsychotics, have a significantly lower chance of causing extrapyramidal disorders, though they primarily induce metabolic side effects, consisting of significant weight changes, glucose metabolism dysregulation, and dyslipidemia. These unwanted drug reactions significantly reduce adherence to therapy and can lead to serious complications in the future. At the same time, experience with the use of atypical antipsychotics has shown that the severity of unwanted reactions differs within the group of atypical antipsychotics and, more importantly, even for one drug taken by different patients, is a variable index. The reason for this phenomenon lies is in the polymorphism of the pharmacokinetic and pharmacodynamic factors involved in the metabolism of atypical antipsychotics and the different chemical structure of the drugs. The study of the effect of various combinations of polymorphic variants of the pharmacokinetic and pharmacodynamics factors on the development of antipsychotic-induced metabolic disorders is a complex and high-priority task of personalized medicine.